2001
DOI: 10.1097/00004647-200108000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Cloned Blood–Brain Barrier Adenosine Transporter is Identical to the Rat Concentrative Na+ Nucleoside Cotransporter CNT2

Abstract: Adenosine transport into brain is regulated by the activity of the adenosine transporter located at the brain capillary endothelial wall, which forms the blood-brain barrier (BBB) in vivo. To facilitate cloning of BBB adenosine transporters, poly A+ RNA was purified from isolated rat brain capillaries for production of a rat BBB cDNA library in the pSPORT vector. The cloned RNA (cRNA) generated from in vitro transcription of this library was injected into frog oocytes followed by measurement of [3H]-adenosine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 25 publications
2
44
0
Order By: Relevance
“…Consumption of UMP (2000 mg) by humans raises plasma uridine levels by 3 fold (from 6.0 to 21.9 μM), for 5-6 hours (Cansev, 2006). Circulating uridine crosses the blood-brain barrier via an adenosine transporter (the concentrative nucleoside transporter type 2; CNT2) (Li et al, 2001), which is unsaturated at physiologic plasma uridine concentrations (Cansev et al, 2005). Thus, dietary UMP can increase brain levels of uridine and subsequently, as shown in gerbils, brain levels of UTP, CTP and CDP-choline (Cansev et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumption of UMP (2000 mg) by humans raises plasma uridine levels by 3 fold (from 6.0 to 21.9 μM), for 5-6 hours (Cansev, 2006). Circulating uridine crosses the blood-brain barrier via an adenosine transporter (the concentrative nucleoside transporter type 2; CNT2) (Li et al, 2001), which is unsaturated at physiologic plasma uridine concentrations (Cansev et al, 2005). Thus, dietary UMP can increase brain levels of uridine and subsequently, as shown in gerbils, brain levels of UTP, CTP and CDP-choline (Cansev et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Brain PtdCho synthesis can be enhanced by its three circulating precursors (Kennedy and Weiss, 1956): choline, a pyrimidine nucleoside like uridine or cytidine, and a polyunsaturated fatty acid (PUFA) like docosahexaenoic acid (DHA) (Araki and Wurtman, 1998;Rapoport, 2001;Marszalek and Lodish, 2005); all three readily cross the blood-brain barrier (Li et al, 2001;Spector, 2001). Brain uridine can be phosphorylated by uridine kinase (Suzuki et al, 2004) to form uridine-5′-triphosphate (UTP), which can be aminated (by CTP synthetase) to cytidine-5′-triphosphate (CTP) (Genchev and Mandel, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…However, the BBB choline transporter is sodium independent 45 and is likely a member of a different SLC gene family. The BBB adenosine carrier transports adenosine, guanosine, and certain pyrimidine nucleosides such as uridine, 46 and is derived from the CNT2 gene, 47 where CNT ϭ concentrative nucleoside transporter. Purine nucleosides are also transported by sodium independent or equilibrative nucleoside transporters (ENT), which are members of the SLC29 gene family (Table 2).…”
Section: Cmtmentioning
confidence: 99%
“…Studies using rodent and human tissues have reported the existence of specific proteins that transport a variety of xenobiotics and endobiotics, such as drugs, flavonoids, metals, nucleotides and nucleosides, di-and tripeptides, and bile acids (Saito et al, 1995;Lomri et al, 1996;Miyamoto et al, 1996;Yao et al, 1997;Suzuki and Sugiyama, 1998;Cousins and McMahon, 2000;Ferguson et al, 2001;Li et al, 2001). The total number of transporters in rodents reported in the literature independent of the discoveries through the genome sequencing projects is about 50, and many more seem to await characterization.…”
mentioning
confidence: 99%